CULTIVO INTERCALAR DE PLANTAS DE COBERTURA NA CULTURA DA PIMENTA-DO-REINO - Silva, Bruno Eustaquio Cirilo (2020)
Espírito Santo stands out on the national scene as the largest black pepper producer in the country. In this region, the exposed soil is often observed, which predisposes the soil to water erosion and a decrease in the organic matter content. The use of c